Somatic Cell Number, Physicochemical, and Microbiological Parameters of Raw Milk of Goats During the End of Lactation as Compared by Breeds and Number of Lactations - Gecaj, Rreze M.; Ajazi, Flutura C.; Bytyqi, Hysen; Mehmedi, Blerta; Çadraku, Hazir; Ismaili, Muharrem (Frontiers in Veterinary Science, 2021)
The aim of this study was the evaluation of somatic cell count (SCC), physicochemical and microbiological parameters during the end of lactation in the raw goat’s milk of Alpine and native Red goat breed. A total number of 102 milk samples from Alpine and native Red goats were included in the experiments. Within the same breed two different groups were analyzed: a group consisting of animals in their first lactation and the second group consisting of animals from the fifth lactation. The milk samples were individually and daily collected during late lactation for three consecutive weeks, and milk fat, protein, lactose, SCC and total bacteria with enterobacteria were assessed. Fresh goats’ milk from late lactation period had a number of somatic cells within the expected value with log10 of 5.8- 6.18 cells/ml for the compared groups. In both breeds the total mesophilic bacteria were fewer in number, however in the native Red goat a larger population of such bacteria was enumerated. The number of coliforms and enterobacteria was below 100 cfu/ml. In our study we were able to show a significant difference among the studied breeds depending on lactation and season for fat (p=0.002), but not for lactose and protein content. A positive correlation for total protein (TP), lactose and fat as well as for lactose and SCC was found in the native Red goat breed. In the Alpine goat breed, a strong positive correlation (0.821**) was found for lactose and enterobacteria count (EC). In conclusion these findings evaluate different goat milk parameters during late lactation period and provide an indirect measure to monitor goat mammary gland health for both breeds.